Existence of Weak Solutions for Caputo’s Fractional Derivatives in Banach Spaces - Akhter, Samima (GANIT: Journal of Bangladesh Mathematical Society, 2019)
The objective of this project is to represent the existence of solutions for Caputo’s fractional derivatives in Banach spaces. The result is based on some well-known fixed point theorems. To show the efficiency of the stated result some examples will be demonstrated GANIT J. Bangladesh Math. Soc.Vol. 39 (2019) 111-118